The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-66918-6
|View full text |Cite|
|
Sign up to set email alerts
|

Magneto-Hybrid Nanofluids Flow via Mixed Convection past a Radiative Circular Cylinder

Abstract: The goal of the current analysis is to scrutinize the magneto-mixed convective flow of aqueous-based hybrid-nanofluid comprising Alumina and Copper nanoparticles across a horizontal circular cylinder with convective boundary condition. The energy equation is modelled by interpolating the non-linear radiation phenomenon with the assisting and opposing flows. The original equations describing the magneto-hybrid nanofluid motion and energy are converted into non-dimensional equations and solved numerically using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 51 publications
(54 reference statements)
0
32
0
Order By: Relevance
“…The partial differential equations (PDE) system ( 7)-( 10) has a multi-scale solution behavior over an infinite interval where the solution varies quickly over the boundary layer and away from this layer the solution varies slowly and behaves regularly and that is according to the time constants of the solution components. Moreover, the PDE system (7)-( 10) is very sensitive to the initial conditions due to the singularity associated with the highest derivative-term in the system and hence more accurate and efficient adaptive methods are required for solving this class of PDE systems [5,[27][28][29][30][31][32]. System ( 7)-( 10) is converted into a first-order PDE system and discretized using a fourth-order finite difference method in η-orientation and a two-point backward finite difference method [28] in τ-orientation.…”
Section: Fourth-order Finite Difference Continuation Methods (Ffdcm)mentioning
confidence: 99%
“…The partial differential equations (PDE) system ( 7)-( 10) has a multi-scale solution behavior over an infinite interval where the solution varies quickly over the boundary layer and away from this layer the solution varies slowly and behaves regularly and that is according to the time constants of the solution components. Moreover, the PDE system (7)-( 10) is very sensitive to the initial conditions due to the singularity associated with the highest derivative-term in the system and hence more accurate and efficient adaptive methods are required for solving this class of PDE systems [5,[27][28][29][30][31][32]. System ( 7)-( 10) is converted into a first-order PDE system and discretized using a fourth-order finite difference method in η-orientation and a two-point backward finite difference method [28] in τ-orientation.…”
Section: Fourth-order Finite Difference Continuation Methods (Ffdcm)mentioning
confidence: 99%
“…Jakeer et al [30] discussed magneto Cu-Al 2 O 3 /water hybrid nanofluid flow in a non-Darcy porous square cavity and found that the Cu-Al2O3/water nanofluid provides a higher heat transfer. MHD convective flow of water-based hybrid-nanofluid containing Alumina and Copper nanoparticles through a horizontal circular cylinder was studied by Zahar et al [31]. Futhermore, Ghalambaz et al [32] investigated nano encapsulated phase change material in a glass ball porous medium, where the nanoparticles comprise of PCM core (nonadecane) and a shell (polyurethane).…”
Section: Analysis Of Platelet Shape Al 2 O 3 and Tio 2 On Heat Generativementioning
confidence: 99%
“…The MHD flow has a wide range of applications in the fields of chemistry and biology, for instance, the fabrication in cancer tumor therapy resulting hypothermia, decreasing bleeding in the state of acute injuries, magnetic resonance visualizing, and various other diagnostic experiments [3]. Magnetohybrid nanofluids flow via mixed convection past a radiative circular cylinder was studied in [4]. The EHD flow of a fluid is modeled by a set of partial differential equations, which can be reduced to an ordinary differential equation as in [16], and results in the following Emden-Fowler type of equation:…”
Section: Model Of Electrohydrodynamic (Ehd) Flow In a Circular Cylindmentioning
confidence: 99%